Analysis of a performance-based functional test in comparison with the visual analog scale for postoperative outcome assessment after lumbar spondylodesis - Hartmann, Sebastian; Hegewald, Aldemar Andres (European spine journal, 2016)
Study design: Prospective, non-blinded, non-randomization. Purpose: Pain scales are commonly used to assess the condition of spine patients, although the degree of correlation between different pain scores, and between the scores and the patients’ functional status is, at best, variable. Pain usually limits physical activities, but there is a lack of a widely accepted tool for investigating pain-related physical impairment in everyday routine work. The purpose of this study was to evaluate and correlate the visual analog scale (VAS) and the “timed up and go” (TUG) test in patients after lumbar spondylodesis. Methods: Thirty-eight patients with degenerative lumbar disease who were treated with monosegmental or bisegmental spondylodesis were included on a consecutive and prospective basis. The VAS and TUG were assessed preoperatively and during the first 12 weeks postoperatively. Special attention was paid to the early follow-up after surgical intervention. Correlations between the two tests were assessed. Results: The VAS showed gradual reduction after surgery, reaching statistical significance on the sixth postoperative day, with significant changes over time from the first to third, third to sixth postoperative days and from the sixth postoperative day to 2 weeks after surgery. In contrast, the TUG demonstrated a significant deterioration in function on the first and third postoperative days, returning to baseline levels thereafter (at postoperative days 6 and 14). Significant improvement in function in comparison with the preoperative status was established after 4 weeks and continued until the last follow-up examination. The TUG showed significant differences between all visits along the timeline. A correlation between the two tests was only observed on the first day after surgery. Conclusion: In summary, the TUG appeared to be significantly more sensitive for describing the course after spine surgery. The TUG represents an appropriate performance-based functional test that is not time-consuming. Assessment of both pain and functionality is, therefore, needed to evaluate patients adequately.
Gesehen am 07.05.2019
Published online: 12 December 2015